Teknik Aplikasi Sampel Pada Pengujian Kuantitatif Kromatografi Lapis Tipis: Tinjauan Terhadap Area Dan Faktor Retensi - Kusumawati, Idha; Primaharinastiti, Riesta; Rifqi Prasetyawan, Hanif (Jurusan Farmasi Poltekkes kemenkes Makassar, 2024)
Thin Layer Chromatography (TLC) is one of the most commonly used chromatographic techniques to identify compounds in mixtures and determine the purity of a compound. However, the crucial factor that is difficult to control, which can affect the accuracy of the results, is the stage of sample application. This study focused on investigating the effect of different techniques of sample application (manual and semi-automatic) on the area and retention factor (Rf) of the compound spot. Curcuminoid was used as a sample in this study. The manual sample application techniques used a 2μL capillary tube. The semi-automatic sample application techniques used a Camag Linomat-5 instrument with 0, 7, and 8 mm band lengths. After the development of the TLC plate using toluene: acetic acid (4:1, v/v)., the curcuminoid was separated into three spots: curcumin, demethoxycurcumin, and bisdemethoxycurcumin. A one-way ANOVA was used to analyze the spot area and Rf of the three compounds, followed by a Duncan test. The difference in sample application techniques causes differences in the size and shape of the initial sample spot, which affects the compound spot produced after developing of TLC plate. This study showed that the differences in application techniques cause significant differences in the Rf of the compound spot, but do not show significant differences in the compound spot area. Based on this research, optimizing the application techniques of samples is a critical stage and it is essential to optimize how to apply the sample on TLC plate, including the concentration, volume, shape, and size of the spot on TLC.